Penerapan CFTT untuk Pengujian Aplikasi Web-Based Android Analysis Tools (WAAT) dengan Federated testing - Yasir Muin; Yudi Prayudi; Fietyata Yudha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The evolutionary of smartphones and their technology simplify human activitie, with the features provided, this development does not rule out the sophistication of smartphone features being used as a medium of communication to support forms of crime. The process of forensic investigations in handling electronic evidence on smartphones is a challenge for forensic experts because of the ever-growing development of smartphones. The problem faced by forensic experts is that it is difficult to determine the forensic tools that should be used in handling evidence because several applications developed have not been tested with forensic standards. For this reason, this research will conduct web application testing based on android analysis tools based on standard computer forensics testing tools using the federated testing application. This test is conducted to determine the feasibility of a web-based application by evaluating the data between the results of the web-based test and the results of the federated testing. From the results of the evaluation, it was found that the web-based application was still lower than the federated testing because the web-based application was only able to produce the same four data variables as the federated testing report, while other data had not been supported by the application, so it could be concluded that the application This web-based android analysis tool does not meet standardization CFTT requirements.